Fire protection durability of intumescent coatings after Iaccelerated aging - Thabet, Rida (2020)
The most common method of achieve the required fire resistance of structures and struc-tural elements is using passive fire protection systems, being the intumescent coatings the fire protection material frequently used. This work presents a research study about the ef-fects of aging on the fire protection performance of intumescent coatings. A commercial water based coating is submitted to an accelerated aging cycle, using a QUV accelerated weathering tester. These tests aim to simulate 10 years of the coating natural aging accord-ing to the European technical approval guideline (ETAG N° 018). The coating durability is tested comparing the fire protection efficiency of small steel samples submitted to a con-stant radiant heat flux exposure from a cone calorimeter as prescribed by the standard ISO 5660. In total, 28 tests were performed on intumescent coating protected steel specimens, in which 14 specimens were tested before the hydrothermal aging test and other 14 after ac-celerated aging. The experimental test results of the steel temperature evolution shows that increasing the intumescent dry film thickness, an increase of the fire resistance time is at-tained. After the accelerated aging cycles, the coating lose their ability to expand, resulting in an increase of the steel temperature of approximately 200 ºC, compared to the samples without aging.